Pekerjaan Kristus dan Pekerjaan Manusia dalam Keselamatan [The Work of Christ and the Work of Man in Salvation] - Setiawati, Riva Diyas (Diligentia: Journal of Theology and Christian Education, 2023)
The understanding of the assurance of salvation does not only affect the way people think, but also the way they live their life. Extreme conclusions that arise from the topic of assurance of salvation can make humans rely on themselves in obtaining salvation or live irresponsibly with guarantees that they will remain saved. This paper seeks to describe the saving work of Christ and human work as the results of salvation. It is concluded that humans are completely dependent on God in obtaining salvation and God Himself is also the one who maintains this salvation until the end of time. However, humans need to work together with God in the process of sanctification and spiritual growth. This awareness of the assurance of salvation should bring gratitude, which is expressed in obedience to God, true service, and preaching of the Gospel. Research method used in this paper is literature review.BAHASA INDONESIA ABSTRACT: Pemahaman akan jaminan keselamatan tidak hanya mempengaruhi cara berpikir manusia, tetapi juga cara mereka menjalani hidup. Kesimpulan ekstrim yang muncul dari topik jaminan keselamatan dapat membuat manusia mengandalkan diri sendiri dalam memperoleh keselamatan, atau hidup tidak bertanggung jawab dengan jaminan bahwa mereka akan tetap selamat. Tulisan ini berusaha untuk menjelaskan karya penyelamatan Kristus dan pekerjaan manusia sebagai hasil dari keselamatan. Disimpulkan bahwa manusia sepenuhnya bergantung pada Tuhan dalam memperoleh keselamatan dan Tuhan sendirilah yang memelihara keselamatan itu sampai akhir zaman. Namun demikian, manusia perlu bekerja sama dengan Tuhan dalam proses pengudusan dan pertumbuhan rohani. Kesadaran akan jaminan keselamatan ini seharusnya membawa rasa syukur yang diekspresikan dalam ketaatan kepada Allah, pelayanan yang benar, dan pemberitaan Injil.